2018
DOI: 10.3382/ps/pey088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of phytase to diets low in inorganic phosphorus on growth performance and mineralization of broilers

Abstract: There has been discussion regarding microbial phytase replacing inorganic phosphorus (P) supplementation in broiler diets. Therefore, an experiment was conducted to examine the effect of phytase supplementation on diets low in inorganic P. Ross 308 broilers (n = 288) were fed one of 6 experimental diets in 4 phases. The control diet had 16.20, 10.90, 9.40, and 6.10 g/kg inorganic P in the Starter, Grower 1, Grower 2 and Finisher phase respectively. The remaining diets had 10.50 g/kg inorganic P in the Starter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…Reduction of inorganic P usage in broiler diets using microbial phytase has been extensively debated (Scholey et al, 2018). Furthermore, previous studies have shown that microbial phytase supplementation in P-deficient diets affect growth performance and bone mineralization of broilers (Anjum et al, 2018;Scholey et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction of inorganic P usage in broiler diets using microbial phytase has been extensively debated (Scholey et al, 2018). Furthermore, previous studies have shown that microbial phytase supplementation in P-deficient diets affect growth performance and bone mineralization of broilers (Anjum et al, 2018;Scholey et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of inorganic P usage in broiler diets using microbial phytase has been extensively debated (Scholey et al, 2018). Furthermore, previous studies have shown that microbial phytase supplementation in P-deficient diets affect growth performance and bone mineralization of broilers (Anjum et al, 2018;Scholey et al, 2018). Waldroup, (1999) noted that broilers fed P-deficient diet supplemented with phytase excreted less P while performance of these broilers Journal of Poultry Science, 57 (1) 32 Pooled standard error of mean CON: control diet (phosphorous-sufficient diet with dicalcium phosphate) LPY: phosphorous-deficient diet with 0.01% phytase (500 FTU/kg) without dicalcium phosphate HPY: phosphorous-deficient diet with 0.02% phytase (1000 FTU/kg) without dicalcium phosphate a, b Means in the same row with different superscripts differ significantly (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Scholey et al (2018) o uso de altas doses de fitase para substituir a suplementação de P inorgânico, possuindo o potencial de reduzir os custos de alimentação.…”
Section: Efeitos Da Fitase Na Alimentação De Frangos De Corteunclassified
“…Exogenous enzymes such as phytase, xylanase, amylase, and protease have been extensively scrutinized during the last two decades in studies designed to demonstrate their efficacy in broiler diets. The inclusion of phytase (PHY) has made a significant reduction of inorganic phosphorus in non-ruminant diets possible without compromising live performance, livability, or carcass traits (Adeola et al, 2004;Beudeker et al, 2005;Pieniazek et al, 2017;Scholey et al, 2018;Leyva-Jimenez et al, 2019). Beyond the capacity of PHY to increase the availability of phosphorus via degradation of the anti-nutritive phytate molecule, this enzyme has demonstrated to increase the availability of other minerals as well as protein and starch.…”
Section: Introductionmentioning
confidence: 99%